The European dilemma: consequences of the new migration on European security and defence - Cerqueira, J. (Revista de Ciências Militares, 2016)
European Union is experiencing its greatest dilemma since setting out on its project. With human rights, democracy and freedom as its political and constitutional identity, EU has been forced to reconsider its strategies in order to defend itself and protect its citizens. Politicians continue to alter the local, regional and communitarian legal system, placing legal barriers – and much more – before non-EU immigrants. This puts the community’s ethos in jeopardy and the fear of the other is changing irreversibly the acquis communautaire, the legal corpus that has taken years to create. The panic and weakness of our political leaders has not reassured the people, nor there has been any evidence of reason or dignity in the search for solutions. The extreme reaction has weakened us all and has also undermined European Union’s political aspirations to be a major global player. The difficulty of assimilating a large number of migrants with strong cultural identities of their own, who share a different religion from the majority of the native population, also presents a challenge to unity. They are accustomed to an anthropological political dialectic of dominated/dominant that is different from the European Union reality. Marginalisation and social exclusion will only increase as a result of the lack of assimilation policies as will xenophobia. Radical political changes will follow these social facts.